Aligning Skills with Jobs. (January 2017) - Chenoy, Dilip
Abstract: India has a young population; 47 per cent of the population is below the age of 24. Over 12.8 million people enter the workforce every year. Only about 10 per cent of the workforce has received some form of either formal or informal training. The training capacity in 2008 was 3.1 million per year. Despite the training capacity and the number of entrants to the workforce, a large number of employers faced difficulty while filling entry-level vacancies. Studies brought out the fact that only about one-third of those completing courses from a variety of educational and training institutes were employable. To address various issues in the skill development space and to involve the employers in the skill sector, in 2008, the Government of India announced the setting up of National Skill Development Corporation (NSDC) as a public–private partnership (PPP). This article brings out the impact of the efforts made by the NSDC to project skill gaps, identify job roles and get employers to lead the process of identifying skill gaps, creating standards for job roles, increasing the skill training capacity and aligning trainings with jobs. The article highlights the work done by Sector Skill Councils (SSCs) and the roll-out of the National Skill Certification and Monetary Reward Scheme (known as STAR), as well as the Pradhan Mantri Kaushal Vikas Yojana (PMKVY), with a view to encourage youth to take up skill programmes that are aligned to specific job roles. This article also reviews the recent initiatives and some of the challenges, and the way forward to aligning skills with jobs.